Occlusion of the Right Ventricular Wall Branch of a Recessive Right Coronary Artery Resulting in Ventricular Fibrillation and Anterior ST-Segment Elevation—A Case Report - Sharma, Harish; George, Sudhakar (Frontiers in Cardiovascular Medicine, 2020)
Background: Right ventricular (RV) infarction is as an extremely rare cause of isolated anterior ST-segment elevation. Occlusion of the RV branch in a recessive RCA causing isolated RV infarction and only anterior ST-elevation is extremely rare. To date, the handful of such cases reports do not describe any arrhythmia associated with this presentation. Although ventricular fibrillation (VF) has been well documented with interruption of flow in the conus branch of the RCA, here we describe VF occurring in a patient with occlusion of the RV branch of a recessive RCA presenting with isolated anterior ST-segment elevation. Case: A 51-year-old man presented with acute chest pain and isolated anterior ST-segment elevation on electrocardiogram (ECG). The patient developed ventricular fibrillation prior to coronary angiography requiring cardiopulmonary resuscitation. Coronary angiography revealed an unobstructed left coronary system and a recessive right coronary artery with ostial occlusion of the RV branch which was treated with a drug eluting balloon, resulting in resolution of the chest pain and ECG changes. Conclusion: Isolated RV infarction due to RV branch occlusion can cause ECG changes mimic anterior left ventricular infarction. This presentation may be complicated by VF, even in the setting of a recessive RCA.